Workshop on Assistance for the Merdeka Belajar Education Unit Curriculum to Improve the Management Competencies of PAUD Teachers in Gugus Teratai, Jati Sampurna District, Bekasi - Sri Watini; Lilis Suryani; Yani Suryani; Erniati R (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Significant challenges in developing the quality of early childhood education (PAUD) in the Gugus Teratai, Jatisampurna District, Bekasi, were identified through several gaps in teachers' ability to design a comprehensive and contextualized Education Unit Curriculum (EUP). Initial studies revealed that 78% of 24 teachers spread across 18 PAUD units had difficulty in developing a curriculum according to the characteristics of their respective institutions. In order to overcome these problems, Community Service (PKM) activitiy was carried out in the form of workshops and assistance in preparing the Education Unit Curriculum in early November, 2024. Activities were designed systematically with a practical and collaborative approach using interactive workshop methods, observation, and direct assistance. The Success evaluation of the program was carried out through pre and post-test instruments. The analysis results showed a significant increase in teacher competence, with an average score increasing from 52,92 to 93,12, indicating an increase in ability of 75,98%. The majority of participants achieved the expected level of competency in curriculum design. The success of this program is not only measured by the increase in scores, but also by the practical ability of participants to develop a curriculum that is in line with the characteristics of PAUD institutions. Therefore, this activity povides a positive contribution in improving the quality of curriculum management and professional development of PAUD teachers in its region.